2016
DOI: 10.5424/sjar/2016143-9433
|View full text |Cite
|
Sign up to set email alerts
|

Changes in productivity in the virgin olive oil sector: An application to Protected Designations of Origin in Spain

Abstract: to the population´s growing concerns related to healthy aspects of food, there is also a growing interest taken in the origin or provenance of products as a source of information and significance in the sale of products and brands (Brugarolas et al., 2010). Without a doubt, one of the most successful formulas that agri-food operators have when it comes to competing in increasingly global markets, consists of emphasising all those aspects related to origin or provenance of products through different figures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Also, the Authors observed that the inefficiency is caused by the fact that the farms do not use minimum input or do not raise the maximum output from the actual inputs. In another study by Aparicio et al (2016), a Luenberger-type indicator based on a specific weighted additive model in DEA was used to estimate and decompose productivity change for Protected Designations of Origin (PDOs) in the Spanish virgin olive oil sector. According to their results, the most productive PDOs were those with an important number of oil mills and packaging/marketing companies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also, the Authors observed that the inefficiency is caused by the fact that the farms do not use minimum input or do not raise the maximum output from the actual inputs. In another study by Aparicio et al (2016), a Luenberger-type indicator based on a specific weighted additive model in DEA was used to estimate and decompose productivity change for Protected Designations of Origin (PDOs) in the Spanish virgin olive oil sector. According to their results, the most productive PDOs were those with an important number of oil mills and packaging/marketing companies.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, it is obvious that the technical efficiency is highly subjective to the choice of the direction vector. To overcome this limitation, we adopt the WADF introduced by Aparicio et al [41] , instead of the DDF, to decompose our revenue Luenberger indicator, defined as:…”
Section: Revenue Luenberger Indicatormentioning
confidence: 99%
“…Efficiency analysis is central to many studies that aim to evaluate the economic performance of olive farms [25][26][27][28][29][30][31] and the olive sector [32,33]. A common methodological approach to estimate the TE of olive groves is data envelopment analysis (DEA), initially developed by Charnes et al [34].…”
Section: Introductionmentioning
confidence: 99%